A response to “On token reinforcement and stuttering therapy: Another view on findings reported by Howie and Woods (1982)” - Howie, Pauline M. (1983)
Ingham's (1983) critique of our research is based on the unwarranted assumption that it claimed to be a replication of Ingham and Andrews' (1973a) study. Our report did not claim to be a replication. Procedural differences between treatments do not preclude the possibility of drawing general conclusions that may apply to related treatments, or suggesting possible confounding variables that might be operating in another study. We have nevertheless dealt with each of Ingham's methodological objections. In general, we believe that we struck an acceptable compromise between the needs of clients and theoretical and research demands. We stand by our original conclusions, and note with satisfaction that Ingham concurs with our emphasis on systematic structure rather than the presence or absence of rewards as the crucial component of this type of stuttering treatment.